Factors Causing Decreasing Quality of Vaccines: A Systematic Review - Naimah, Naimah; Setyaningsih, Wahyu; Mansur, Herawati; Agustia, Dilma'aarij; Maulidia, Miftakul Fira (Jurnal Kesehatan Masyarakat, 2024)
Abstract. Objectives. Vaccines were essential to prevent the spread of disease. The contents would be practical if the storage, distribution, handling, and delivery to the target were carried out correctly and following procedures. Methods. Using guidelines from the PROSPERO platform using the PRISMA flow diagram to select articles. The search keywords are observational studies, experiments, qualitative studies, and grey literature. Studies addressing factors affecting vaccine quality, published between 2009 and 2022 in English, were included.  Results. Of the 13 included studies, several factors were identified, all explained due to inaccurate vaccine storage temperature settings. From several studies, it is recommended to carry out consistent SOPs, supervision, training for staff involved in vaccines, innovation of vaccine distribution tools, and policies from local government stakeholders.